Role of Immunohistochemistry in The Subtyping of Non Small Cell Lung Carcinoma on True Cut Lung Biopsies - M, Alekhya; N, Rukmangadha; AY, Lakshmi; M, Manickavasagam (Annals of Pathology and Laboratory Medicine, 2018)
BACKGROUND: Worldwide, lung carcinoma is the most common cancer in terms of number of cases and deaths. Lung carcinomas are broadly divided into small cell carcinoma and non-small cell lung carcinoma(NSCLC). In recent years availability of targeted therapies necessitated subtyping the NSCLC to improve the survival and quality of life. NSCLC can be subtyped by routine Haematoxylin and Eosin (H&E) stained section slides alone, poorly differentiated tumors are difficult to segregate morphologically, especially in true-cut biopsies, necessitating ancillary techniques like immunohistochemistry (IHC). Hence this study was taken up to examine accuracy of diagnosis of Non-Small Cell Lung Carcinoma (NSCLC) on biopsy samples initially made based on morphology and then with IHC using relevant markers like CK5, CK6, CK7, Napsin-A, TTF-1, P63, Synaptophysin and Chromogranin-A. METHODS: A prospective study of two years and six months duration during which 111 cases of NSCLC on true-cut biopsies were first reported on Haematoxylin and Eosin sections and later subjected for IHC. RESULTS: Out of 111 cases, after IHC, 80 were diagnosed as adenocarcinoma and 31 as squamous cell carcinoma NSCLC were common in the 6th decade. In adenocarcinoma positivity for CK7, TTF1 and Napsin-A was 95%, 75%and 78.75% respectively. In squamous cell carcinoma positivity for CK5, CK6 and P63 was 84%, 81% and 90% respectively. CONCLUSION: CK5, CK6 and P63 can be used for confirming squamous cell carcinoma and CK7, TTF-1 and Napsin-A for adenocarcinoma. We recommend a IHC panel consisting of P63, TTF1 and Napsin-A in NSCLC-unclassifiable and poorly differentiated carcinoma on H&E.